2020
DOI: 10.1159/000508028
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of Stent Retriever Length to Clot Extent Affects First-Pass Reperfusion in Endovascular Treatment of Acute Ischemic Stroke

Abstract: Background: Stent retriever technology has evolved, and significantly longer devices have become available for mechanical thrombectomy (MT) of large cerebral vessel occlusions in ischemic stroke. We hypothesized that increased stent retriever length may improve the rate of complete angiographic reperfusion and decrease the respective number of attempts, resulting in a better clinical outcome. Methods: Retrospective analysis of patients with large vessel occlusion in the anterior and posterior circulation treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…On the contrary, comparing lengths of stents (short: 4 × 20 mm and long >20 mm: 4 × 40, 6 × 30, or 4 × 30), Styczen et al (17) found comparable FP TICI 3 for both short and long stent retrievers in MCA (50.8 vs. 40.7%) occlusions with higher mFP in short vs. long stent retrievers (50.8 vs. 40.7%, p = 0.024). But long retrievers achieved a higher rate of successful reperfusion (TICI ≥2b) with higher rate of SAH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, comparing lengths of stents (short: 4 × 20 mm and long >20 mm: 4 × 40, 6 × 30, or 4 × 30), Styczen et al (17) found comparable FP TICI 3 for both short and long stent retrievers in MCA (50.8 vs. 40.7%) occlusions with higher mFP in short vs. long stent retrievers (50.8 vs. 40.7%, p = 0.024). But long retrievers achieved a higher rate of successful reperfusion (TICI ≥2b) with higher rate of SAH.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro , it was reported that longer stent retrievers (6 × 40 vs. 6 × 30) achieve higher FP in fibrin-rich clots ( 15 ). On the contrary, one study comparing diameter (4 vs. 6 mm) found no difference in reperfusion rate of ICA, MCA, and anterior cerebral artery (ACA) occlusions ( 16 ), and others found higher rates of modified FP (mFP) (TICI ≥2b) in the MCA with short stent retrievers (20 mm vs. others) ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in LVO, the largest possible stent-retriever should be chosen for the first thrombectomy attempt (25,27).…”
Section: Discussionmentioning
confidence: 99%
“…Angiographic revascularization was assessed using the modified thrombolysis in cerebral infarction (TICI) score in the final run of the angiography, measuring reperfusion in the downstream territory of the specific arterial occlusion, as follows: grade 0 = no reperfusion; grade 1 = antegrade reperfusion past the initial occlusion, but with limited distal branch filling and little or slow distal reperfusion; grade 2a = antegrade reperfusion of less than half of the occluded target artery previously ischemic of the downstream territory; grade 2b = antegrade reperfusion of more than half, but <90% complete antegrade reperfusion; grade 2c = near-complete reperfusion (90–99%) except for slow flow in a few distal cortical vessels or the presence of small distal cortical emboli; and grade 3 = complete antegrade reperfusion with the absence of visible occlusion in all distal branches [ 14 , 18 , 23 , 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%